(3eHGOF GdJShjb GdRQGYj (B/s - (3YGca, GdRYHjs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2006)
(3GdJShjb heHGOFg GdCSGSjI(B-(3GdJShjb GdRQGYj(B-(3hXGFa GdJShjb GdRQGYj(B-(3bfhGJ GdJShjb(B-(3JcGdja hghGeT GdJShjb(B-(3CShGb GdLedI(B-(3eDSSGJ Ch efXeGJ GdJShjb GdCgdjI hTHg GdMchejI(B-(3eOGNd OQGSI GdJShjb(B-(3GdCOGA GdJShjbj dJLGQI GdLedI hbhGYO Jbjjeg(B- (3OhQ GdMcheI aj GdJShjb(B-(3SjGSGJ GdJShjb GdRQGYj defXeI GdJLGQI GdYGdejI (BWTO-(3SjGSGJ GdJShjb GdRQGYj aj GdCQOf(B.s
Keywords: (3GdJShjb GdRQGYjs; (3SjGSGJ GdJShjbs; (3efXeGJ GdJShjbs